(untitled) (Neo Science Peer Reviewed Journal, 2025)
Clothing does not completely repeat the shape of the body surface and clings to one or another part of the body in different ways. It is known that the degree to which the clothing clings to the body in the chest, waist, and hips determines the shape of the figure. The shape of the clothing is also characterized by the width of the shoulders and height of the model’s hem. Regardless of how much the clothing clings to the body, its internal dimensions are larger than the dimensions of the human body. Therefore, the dimensions of the body alone are not enough to draw up a drawing of the basis for the design of the clothing.